Developing the Leaders Around You - Maxwell, John C., 1947- (Nashville Thomas Nelson, 1995)
This classic book by John C. Maxwell takes personal leadership to the next level by demonstrating how to identify and train potential leaders and foster a productive team spirit.
Include Notes
Keywords: Leadership -- Mentoring